Measurement of early maladaptive schemas in heroin addicts treated with methadone in north of Morocco - Semlali Wafae Idrissi; Tarik Ghailan; Ahmed Ahami; Fatima-Zahrae Azzaoui; Khadija Karjouh; Khaoula Mammad (MDPI AG, 2018)
The Early Maladaptive Schema (EMS) are the cognitive structures and the set of processes guiding our behaviors by serving the filtering and the treatment of the information, these dysfunctional schemas have a close relationship with the additive behaviors. The aim of this work measuring EMS in heroin addicts undergoing methadone treatment as well as making a comparison between the activation of the schemas before and after treatment. The present study was carried out on 101 Moroccan patients in a medicopsychological center in Tangier with 85 men and 16 women (mean age was 35), having been diagnosed with opioid dependence described in the DSM-V. EMS were measured using Young's questionnaire short version with 13 schemas. The results showed difference between the activation of schemas in the preand post-treatment (difference=21, CI=11.07-10.63, p<0.001) with an activation of the schema Fear of losing control (M=166.86 (65.3%). In addition Unrelenting standards schema that is significant in men (t=1.97, p=0.048), against emotional deprivation and vulnerability with women (t=4.56, p≤0.001), for the correlation between age and EMS was low, except for the schema of losing control which is highly correlated with age (R=0.55, p≤0.001). Thus, the substance abuse and personality disorders are often coexisting, confirming in part the hypothesis put forward by Ball and Young, which postulates that individuals displaying criteria of substance abuse have an activation of inappropriate schemas of insufficient self-control or Entitlement/Grandiosity.